Patients' Interest in Shared Medical Records (Bangladesh Medical Journal, 2010)
To determine the proportion of patients who are interested in examining their medical records, the personal characteristics related to their interest, and the reasons for their interest. This descriptive cross sectional study was conducted among randomly selected 110 inpatients in a tertiary level hospital. Data were collected through face- to- face interview using one pretested semistructured questionnaire as the research instrument. Collected data were processed, and analyzed by using the SPSS software Version 11.0. The study was conducted in inpatients departments of Comilla Medical College Hospital during May- June2007. Male patients were more interested (85 out of 90) than female (7 out of 20) patients to anticipate the benefits of shared medical records and they were also somewhat more likely to anticipate problems with shared records. Significant predictors of sharing medical records by the patients were anticipation of improving the patient's adherence to their doctor's recommendations (90%) , improving understanding of own medical condition (88%), anticipation of increasing patient's trust in physicians(95%) and anticipation of being reassuring (85%). Shared medical records are almost universally endorsed across a broad range of socioeconomic groups. Patients' interest in reading their medical record is better predicted by their consumer approach to health care. A group of patients were also interested in Internet-accessible records. Key words: Shared medical records; patient access; physician-patient relation DOI: 10.3329/bmj.v39i1.6225 Bangladesh Medical Journal 2010; 39(1): 3-6